Pengaruh Pengembangan Karir, Promosi Jabatan dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada PT. Pema Banda Aceh - Khairan, Uliya; Amelia Rahmi; Yuslaidar Yusuf (Jurnal Sains dan Ilmu Terapan, 2026)
This study aims to analyze the influence of career development, job promotion, and work environment on employee job satisfaction at PT. PEMA Banda Aceh. The method used in this study is quantitative analysis with a multiple linear regression approach. The population of the study consists of all employees of PT. PEMA Banda Aceh, totaling 113 people, with a sample of 88 employees selected as respondents. The sampling technique used is purposive sampling, which involves selecting samples intentionally based on certain criteria. Primary data was collected through the distribution of questionnaires containing questions about career development, job promotion, work environment, and job satisfaction. The results show that job promotion and work environment have a positive and significant effect on employee job satisfaction at PT. PEMA Banda Aceh. Employees who receive job promotions tend to feel more satisfied with their work, as does a conducive work environment. However, career development does not have a significant impact on employee job satisfaction.